Dimensions of tinnitus-related complaints reported by patients and their significant others: protocol for a systematic review - Haider, Haula (2018)
Introduction: Over 70 million people in Europe and textgreater 50 million people in the USA are reported to experience tinnitus (the sensation of noise in the absence of any corresponding sound source). Tinnitus is a multidimensional concept. Individual patients may report different profiles of tinnitus-related symptoms which may each require a tailored management approach and an appropriate measure of therapeutic benefit. This systematic review concerns the patient perspective and has the purpose to find what symptoms are reported by people who experience tinnitus and by their significant others. Methods and analysis: This protocol lays out the methodology to define what dimensions of tinnitus-related symptoms patients and their significant others report as being a problem. Methods are defined according to the Preferred Reporting Items for Systematic reviews and Meta-analyses for Protocols (PRISMA-P) 2015 and data will be collated in a narrative synthesis. Findings will contribute to the eventual establishment of a Core Domain Set for clinical trials of tinnitus. Ethics and dissemination: No ethical issues are foreseen. Findings will be reported at national and international ENT and audiology conferences and in a peer-reviewed journal.